The Evolution of Walt Whitman. - Asselineau, Roger (University of Iowa Press, 1999)
Now, nearly forty years after its original translation into English, Roger Asselineau's complete and magisterial biography of Walt Whitman will remind readers of the complex weave of traditions in Whitman scholarship. It is startling to recognize how much of our current understanding of Whitman was already articulated by Asselineau nearly half a century ago. Throughout its eight hundred pages, The Evolution of Walt Whitman speaks with authority on a vast range of topics that define both Whitman the man and Whitman the mythical personage. Remarkably, most of these discussions remain fre.